New Zealand radiation therapists' perceptions of peer group supervision as a tool to reduce burnout symptoms in the clinical setting. Issue 3 (20th May 2020) - Dungey, Gay; Neser, Hazel; Sim, Dalice
Abstract: Introduction: Research indicates that radiation therapists (RTs) are at risk of burnout and that there is a lack of evidence on effective coping strategies for managing work‐related stressors within this workforce. Peer group supervision (PGS) is a useful tool in assisting staff to manage stress in the clinical setting, improve reflective practice and provide support. The aim of this research was to investigate New Zealand (NZ) RTs' perceptions of participating in PGS. Methods: In‐service training on PGS was offered to all RT centres in NZ, and five of the nine centres agreed to partake in PGS. Participants anonymously completed the same online questionnaire, six months apart. The questionnaire consisted of the Clinical Supervision Evaluation Questionnaire (CSEQ), an open‐ended question and demographics. The CSEQ asks participants to indicate their agreement with 14 statements related to Purpose, Process and Impact of PGS. Results: Overall, 71 and 48 participants completed the first and second surveys, respectively. In contrast to previous studies, this study found that confidence in practice, team support and group safety were valued by participants. This was supported by the qualitative data that revealed four themes: supportive groups, time out to reflect, organisational barriers and group process issues. RTs with one to five years' experience were more likely to structure their meetings, understand the purpose of the meetings and had clearer expectations of the group process. Conclusions: PGS may address burnout for RTs with one to five years' experience. This group of RTs feel patient‐related matters can be discussed openly during PGS, and PGS appears to be helping to improve their practice and reduce stress. More experienced RTs appear to be using the groups as a 'professional support group', rather than 'peer supervision', as a strategy for managing organisational stressors associated with burnout. Abstract :